Possible relevance of epidermal growth factor as a biomarker of inflammation in severe COVID-19 - Pérez Hernadez, Héctor José; Crombet Ramos, Tania (Revista Cubana de Medicina Tropical, 2025)
Background: EGFR plays a critical role in inflammation at the pulmonary level. Data exploring the role of its canonical ligand are scarce. Exploration of new and potential biomarkers expands diagnostic and therapeutic options, providing resilience in complex healthcare settings. Aim: To explore the variability of serum EGF levels according to sex, age and clinical status in subjects with COVID-19 vs. control, as well as to determine possible notable correlates. Methods: Controlled cross-sectional exploratory study with quota sampling in patients with COVID-19 admitted to the Saturnino Lora Hospital. The commercial kit UMELISA EGF from the Cuban Immunoassay Center was used for EGF determinations. Results: Significant differences were observed with respect to serum EGF values in COVID-19 vs. controls (g = 0.6603, p = 0.0021). Serum EGF values < 200 pg /mL were associated with the risk of worse clinical status (OR = 30.8, HR = 11.19 CI95%: 1.82-10.79, X2 = 17.42, p = 0.000*). No biologically relevant differences were observed between sexes (p=0.7694); Regarding age, slight differences in the effect were observed (g = 0.4232, p = 0.0527). A higher probability of obtaining serum EGF values > 200 pg /mL was identified in patients ≤ 65 years (HR = 2.5 CI95 %: 1.06-3.03, p = 0.0308). Serum EGF in relation to NLR (β = 0.2232, p = 0.0353) and PLR (β = 0.2117, p = 0.0411) behaved as a predictor of inflammation in that condition. Conclusions: Serum EGF determination may be a presumed independent marker of inflammation with implications for the pathophysiology of SARS-CoV-2 pneumopathy.